(untitled) (CIPEEX, 2025)
Introduction: The relationship between the brain and the gut has been a topic of great relevance in scientific research. The relationship is based on a vast communication network, and imbalances in this connection can lead to the development and evolution of depression. Objective: This literature review aims to correlate the brain-intestine axis and depression. Methodology: This is an integrative literature review in which the articles used were extracted from the PubMed platform: PubMed, using as descriptors: “Brain-Gut”, “Depression” and “Central Nervous System” (CNS). Articles in English and Portuguese from 2019 onwards were used. Non-free papers, doctoral and master’s theses and articles that did not specifically converge with the guiding question were excluded. After screening, 4 articles were selected for review. Results: Authors recognize that the brain-intestine axis influences the CNS through neural, hormonal, immunological and gastrointestinal signals. Changes in the microbiota can cause inflammation and increased intestinal permeability, activating nerve pathways that regulate the CNS and the enteric nervous system producing inflammatory cytokines, characteristics observed in depressed patients. Increased intestinal permeability allows bacterial products to interact directly with the CNS, since the intestinal microbiota can modulate neurotransmitters such as serotonin, dopamine and GABA, interacting with the brain-gut axis, contributing to depression. Conclusion: It is concluded that there is a strong connection between the gut microbiota and depression, therefore, modulation of the brain-gut axis enables a novel therapeutic approach for gastrointestinal and psychiatric disorders, such as depression.